Acute Colonic Pseudo-Obstruction - Arthur, Thomas; Burgess, Adele (Clinics in Colon and Rectal Surgery, 2022)
Acute colonic pseudo-obstruction (ACPO) is a functional disorder of the large intestine distinguished by colonic dysmotility resulting in colonic distension in the absence of mechanical obstruction. The underlying pathophysiology of ACPO remains unclear despite technological advances in understanding the physiology of colonic motility, such as spatio-temporal mapping and high-resolution manometry. In many ways, the management of ACPO has remained relatively unchanged for 40 years. Patients with perforation or suspected ischemia undergo operative intervention, while patients without undergo initial conservative management with bowel rest, correction of electrolyte disturbances, and mobilization. Patients who fail conservative management or have prominent cecal dilatation undergo decompression with either neostigmine or colonoscopy. A subset of patients with ACPO will have recurrent symptoms despite endoscopic and medical management. For these patients who are difficult to manage, an underlying colonic functional disorder, such as slow-transit dysmotility or chronic intestinal pseudo-obstruction may be considered. The following review of ACPO aims to provide a concise update of the causes, diagnosis, and management of this emergency surgical condition.
Keywords: acute colonic pseudo-obstruction; Ogilvie's syndrome; large bowel obstruction; colonic ileus